Ancaman dan Faktor-Faktor yang Mendorong Swedia Bergabung dengan NATO pada Tahun 2024 - Saputra, Aji Irvan; Indrawati, Indrawati (Jurnal Ilmu Sosial dan Ilmu Politik (JISIP), 2024)
Sweden maintained its neutrality in response to its history, including during the Napoleonic wars, by adopting â€œneutralityâ€ as its official policy in 1834. This neutrality was upheld during both World Wars to protect trade interests. During the Cold War, Sweden chose the path of peaceful diplomacy and rejected military alliances. But Sweden experienced concerns over the Russia-Ukraine conflict and Russia's intervention in Crimea. In May 2022, Sweden eventually applied for NATO membership in response to Russia's invasion of Ukraine in February 2022. This research aims to understand the reasons behind Sweden's decision to join NATO. The factors behind Sweden's decision to join NATO are analyzed using qualitative research methods and through the lens of Threat Perception concept. This research discusses the factors behind Swedenâ€™s decision to join NATO through five dimensions from the Threat Perception concept: structural, geopolitical, historical, socio-cultural, and economic. This research indicates that these five dimensions influenced Sweden's decision to join NATO. Firstly, Swedish ministers and political parties in Sweden played a role in the decision-making process. Secondly, Sweden's geographical location and the rising activities in the Baltic Sea also influenced its decision. Thirdly, Sweden's historical relationship with NATO compared to its relationship with Russia also influenced the decision. Fourthly, the ethnic, cultural, and religious composition of people in Sweden, along with policymaker adoption, are believed to have played a significant role in Sweden's foreign policy formation. Finally, the economic benefits of joining NATO were also considered by Sweden.Swedia telah menjaga netralitas sebagai respons terhadap sejarahnya, termasuk perang Napoleon, dengan mengadopsi kebijakan resmi pada tahun 1834. Netralitas ini dipertahankan selama kedua Perang Dunia untuk melindungi kepentingan perdagangan. Selama Perang Dingin, Swedia memilih jalur diplomasi damai dan menolak aliansi militer. Namun, Swedia mengalami kekhawatiran atas konflik Rusia-Ukraina dan intervensi Rusia di Crimea. Pada tahun 2022, Swedia akhirnya mengajukan keanggotaan NATO sebagai respons atas invasi Rusia ke Ukraina pada bulan Februari 2022. Penelitian ini bertujuan untuk memahami alasan di balik keputusan Swedia untuk bergabung dengan NATO. Faktor-faktor yang mendorong keputusan Swedia untuk bergabung dengan NATO dianalisis menggunakan metode penelitian kualitatif dan melalui lensa konsep â€œpersepsi ancamanâ€. Studi ini membahas faktor-faktor tersebut melalui lima dimensi: struktural, geopolitik, sejarah, sosial-budaya, dan ekonomi. Temuan penelitian menunjukkan bahwa kelima dimensi tersebut memengaruhi keputusan Swedia untuk bergabung dengan NATO. Pertama, Menteri dan partai politik di Swedia berperan dalam proses pengambilan keputusan Swedia bergabung dengan NATO. Kedua, lokasi geografis Swedia dan aktivitasnya di Laut Baltik juga memengaruhi keputusan tersebut. Ketiga, hubungan historis Swedia dengan NATO dibandingkan dengan hubungannya dengan Rusia juga memengaruhi keputusan tersebut. Keempat, komposisi etnis, budaya, dan agama di Swedia, bersama dengan adopsi kebijakan oleh pembuat kebijakan, diyakini memainkan peran penting dalam pembentukan kebijakan luar negeri Swedia. Terakhir, manfaat ekonomi dari bergabung dengan NATO juga dipertimbangkan oleh Swedia.